Pengaruh Kontrol Diri Dan Kecerdasan Emosional Terhadap Kinerja Pegawai ASN Satuan Polisi Pamong Praja Kabupaten Karawang - Amelia, Destriani Nanda; Sari Marliani; July Yuliawati (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of self-control and emotional intelligence on the performance of civil servant employees (ASN) at the Civil Service Police Unit (Satpol PP) in Karawang. Using a descriptive, quantitative, and verificative approach, the research involved 103 employees as both the population and sample, with data collected through questionnaires and interviews and analyzed using path analysis with SPSS. The findings indicate that self-control obtained a total score of 4,414 with an average of 441, categorized as "strongly agree," while emotional intelligence scored 5,222 with an average of 435, also categorized as "strongly agree." Employee performance scored 5,177 with an average of 431, categorized as "agree." Partially, self-control has a positive and significant effect on employee performance (t = 2.126 > 1.984, Sig. = 0.036 < 0.05), as does emotional intelligence (t = 2.171 > 1.984, Sig. = 0.032 < 0.05). Simultaneously, both variables significantly influence employee performance (F = 56.449 > 3.09, Sig. = 0.000 < 0.05). These results highlight the crucial role of self-control and emotional intelligence in improving employee performance within the Satpol PP organization.